Biological insights into alleviating heavy metal toxicity through the simultaneous supply of biochar biofilters derived from the Mikania micrantha and molybdenum nanoparticles - Muhammad Shoaib Rana; Hongyu Chen; Shiwen Deng; Muhammad Imran; Yousif Abdelrahman Yousif Abdellah; Wanting Li; Jiayu Lin; Jiaxi Li; Ruilong Wang (Biochar)
Abstract Cadmium (Cd) contamination in the environment is widespread, making it crucial to reduce Cd accumulation in cereal crops like wheat. However, strategies that not only mitigate Cd pollution but also address other environmental challenges, such as invasive species management, remain unclear. This study introduces an innovative approach combining molybdenum nanoparticles (Mo NPs, 1 µM) and biochar biofilters derived from the invasive plant Mikania micrantha (IPMM), targeting the biochemical and molecular responses of wheat under Cd stress (100 µM). Our findings showed that this novel combination significantly improved wheat physiological characteristics, growth, root architecture, elemental profile, osmoregulation, carotenoid, chlorophyll, gas exchange, and photosynthetic efficiency. Remarkably, simultaneous supply of IPMM biochar biofilters and Mo NPs substantially modulated the Cd translocation, reducing its accumulation in root (30.54%) and shoot (53.59%). Additionally, this strategy not only preserved mesophyll cell structures and the membrane integrity, but also strengthened and activated the oxidative defense systems through the regulation of genetic expressions. This synergistic approach advances the Cd alleviating techniques and offers a sustainable solution for utilizing invasive plants as a potential resource. By addressing both heavy metal pollution and ecological challenges, it provides a promising solution for safer crop production in Cd-contaminated environments. Graphical Abstract